Youth Empowerment: Case Study of West Kalimantan GenRe Ambassador Program 2024 - Apriza, Dwi Kartini; Fernando, Joshua; Supiyandi, Andi (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
The GenRe Ambassador Program in West Kalimantan strategically empowers teenagers, particularly by increasing their knowledge of reproductive health, building mutually supportive communities, and encouraging them to act as agents of change in their communities. This research aims to analyze the program's implementation using a participatory communication theory approach, involving two-way dialogue, active participation, heteroglossia, and dialogical interaction. This study was conducted using a qualitative method with a case study approach. Data were collected through in-depth interviews with six informants, including the West Kalimantan GenRe Forum Chair, GenRe Ambassadors, and other active members. Direct observations were also made to understand the program's dynamics. The study is based on participatory communication theory developed by Bessette (2004), which emphasizes the importance of active community involvement in development through dialogical and inclusive communication. The results show that the program increased teenagers' awareness of life planning and reproductive health, strengthened two-way dialogue, and built supportive social networks. However, social stigma surrounding discussions of reproductive health and limited facilities remain as challenges that need to be overcome. The implications of this research support the achievement of the SDGs, particularly SDG 3 (Good Health and Well-Being), SDG 4 (Quality Education), and SDG 5 (Gender Equality). With further support from the government and society, this program has great potential to evolve into a more effective and inclusive youth empowerment platform.